Aspalathin from Rooibos (Aspalathus linearis): A Bioactive C-glucosyl Dihydrochalcone with Potential to Target the Metabolic Syndrome - Johnson, Rabia; Beer, Dalene de; Dludla, Phiwayinkosi V.; Ferreira, Daneel; Muller, Christo J. F.; Joubert, Elizabeth (Planta Medica, 2018)
Aspalathin is a C-glucosyl dihydrochalcone that is abundantly present in Aspalathus linearis. This endemic South African plant, belonging to the Cape Floristic region, is normally used for production of rooibos, a herbal tea. Aspalathin was valued initially only as precursor in the formation of the characteristic red-brown colour of “fermented” rooibos, but the hype about the potential role of natural antioxidants to alleviate oxidative stress, shifted interest in aspalathin to its antioxidant properties and subsequently, its potential role to improve metabolic syndrome, a disease condition interrelated with oxidative stress. The potential use of aspalathin or aspalathin-rich rooibos extracts as a condition-specific nutraceutical is hampered by the limited supply of green rooibos (i.e., “unfermented” plant material) and low levels in “fermented” rooibos, providing incentive for its synthesis. In vitro and in vivo studies relating to the metabolic activity of aspalathin are discussed and cellular mechanisms by which aspalathin improves glucose and lipid metabolism are proposed. Other aspects covered in this review, which are relevant in view of the potential use of aspalathin as an adjunctive therapy, include its poor stability and bioavailability, as well as potential adverse herb-drug interactions, in particular interference with the metabolism of certain commonly prescribed chronic medications for hyperglycaemia and dyslipidaemia.
Keywords: Aspalathus linearis; Fabaceae; aspalathin; metabolic syndrome; oxidative stress; molecular mechanism; bioavailability; herb-drug interactions